2006
DOI: 10.1016/s1556-0864(15)30357-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy for Chinese Non-small Cell Lung Cancer Patients Who Failed Previous Chemotherapy

Abstract: Our aim was to determine the appropriate salvage regimen for Chinese non-small cell lung cancer (NSCLC) patients who failed previous chemotherapy. We retrospectively analyzed data from our seven clinical trials, including single-agent gemcitabine, gefitinib, docetaxel with a different schedule, vinorelbine plus cisplatin, vinorelbine plus gemcitabine, docetaxel plus gemcitabine, and docetaxel plus ifosfamide, with a total of 342 cases (including 314 patients, of which 28 entered two different trials due to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The OS of combination treatment also showed a moderate improvement comparing with mono-chemotherapy in some studies [20,21]. Several studies also indicated that doublet chemotherapy was a feasible treatment, especially for those patients who had a good PS and had administered targeted drugs in first-or second-line treatment [22]. So far, we have not yet found out whether there is continuously increasing PFS for advanced NSCLC with third-line or further-line treatment and improvement in cancer-related symptoms for doublet chemotherapy patients.…”
Section: Discussionmentioning
confidence: 98%
“…The OS of combination treatment also showed a moderate improvement comparing with mono-chemotherapy in some studies [20,21]. Several studies also indicated that doublet chemotherapy was a feasible treatment, especially for those patients who had a good PS and had administered targeted drugs in first-or second-line treatment [22]. So far, we have not yet found out whether there is continuously increasing PFS for advanced NSCLC with third-line or further-line treatment and improvement in cancer-related symptoms for doublet chemotherapy patients.…”
Section: Discussionmentioning
confidence: 98%